Show-and-tell, Flat Stanley! - Brown, Jeff, 1926-2003; Houran, Lori Haskins (I can read book., 2014)
Participating in an exciting show-and-tell day during which Miss Plum shows the class her sparkly new engagement ring, Flat Stanley is on the case when the ring goes missing.